Labor Versus Empire - Gonzalez, Gilbert G.; Fernandez, Raul A.; Price, Vivian; Smith, David (Taylor & Francis, 2004)
The essays in this collection address issues significant to labor within regional, national and international contexts. Themes of the chapters will focus on managed labor migration; organizing in multi-ethnic and multi-national contexts; global economics and labor; global economics and inequality; gender and labor; racism and globalization; regional trade agreements and labor.